STRATEGI KOMUNIKASI DALAM UPAYA ADVOKASI KOMUNITAS KRETEK TERKAIT PERATURAN PEMERINTAH NOMOR 109 TAHUN 2012 - , INDI FALACHIYYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cigarette and kretek as a product of tobacco has created a long controversy amidst Indonesian society. Majority of public saw tobacco as consumption goods with enormous harm and haram. Thatâs why, in order to save the future of our nation, the government proposed Government Regulation number 109 years 2012 about tobacco controls. However, during its implementation this policy faced various troubles. This Government regulation is opposed by various communities who are harmed by this policy. Kretek community is one of the communities with consciences and commitment to defend the rights of multiple societies who are harmed by PP 109/2012 through advocacy. Kretek community performed advocacy effort through communcation strategy which is expected to achieve their goals. Communication strategy in advocacy effort is a planning and management process with a big goal to achieve, from changing mindset of the people about kretek to persuade government to withdraw PP 109/2012. In order to achieve these goals, they need consistent and prolonged communication effort, since changing the long established perception about a âtruthâ is not easy. Thatâs why this research is conducted in order to understanding communication strategy in advocacy effort related to PP 109/2012 which is done by Kretek community. Communication strategy under advocacy effort is examined through communication action strategy in advocacy Valerie Miller that consists of persuasive strategy, cooperation, litigation and opposition as well as behavior change theory Kurt Lewin which is cognitive field theory. The research showed communication strategy under advocacy effort that are conducted by Kretek community including stakeholdersmapping, opposition and allies and strategic planning inside it including communication activity under management advocacy, from planning stage, implementation and evaluation. Four of the communication strategies for advocacy effort have been conducted by Kretek community. Persuasion strategy, coordination and opposition are the most coordinated and strategic in communication activities of advocacy effort. Meanwhile, litigation strategy is not yet conducted so there is no judicial reviewto retract PP 109/2012 which is the final goal of advocacy effort. In conclusion, communication strategy under advocacy effort of Kretek community has not yet succeeded in persuading government since there is not much support from the society.